The Development of Android-based Augmented Reality Learning Media for Three Dimensional Curved Surface - Sunita Indira; Mangaratua Simanjorang (Jurnal Fibonaci: Jurnal Pendidikan Matematika, 2022)
The objective of this study are developing the valid Augmented Reality (AR) learning media in Android platform for three dimensional curved surface  and getting the students responses. This study was using the type of Research and Development (R&D) with the ADDIE model ( Analysis, Design, Development, Implementation, Evaluation). The data collection technique was using the questionnaire, which used to validating the media and getting the students responses. The validation was obtained from lecturer in State University of Medan  as the material experts and media experts. The media have been implement to the students in the 3rd grade of SMP Negeri 35 Medan. The result of this study show that the AR learning media is the very valid learning media in accordance to the total score percentage of material experts (81,25%) and media experts (82,14%). The students was responsing that the AR learning media in excelent category in accordance to the total score percentage of students responses (85,88%). Therefore, based on the validation, the validity of the android-based augmented reality learning media for three dimensional curved surface has been tested